The Impact of Purpose as a Principal Leadership Skill on the Performance of Select Township Schools in South Africa - Marais, P.; Govender, Krishna K. (International Review of Management and Marketing, 2022)
This study aimed to investigate the impact of “purpose” as a principal leadership skill on the performance of two township schools using a quantitative research design and collecting data from the school principals, teachers and matric learners, using the 28-scale Servant Leadership Test as well as Gallup’s Q12 Employee Engagement survey. The questionnaires addressed the key objectives, namely, the extent to which the principals of the participating schools exhibited servant leadership and their understanding of “purpose” as one word in leadership and how teachers and learners perceived the impact of a “one-word” purpose-driven leader on the performance of the selected schools. Although no relationship could be demonstrated between ‘’purpose’’ and the performance of the two township schools, it became evident that a significant increase in Servant Leadership leads to a significant increase in engagement and performance, as measured by the matric pass rate. It is recommended that workshops be facilitated with principals and teachers in order to entrench ‘’purpose’’ deeper throughout the schools. In addition, Servant Leadership training has to conduced to increase the leadership ability of the school principals. Future research in the area of ‘’purpose as one word’’, as well as Servant Leadership as a principal skillset within the South Africa’s public school’s leadership is recommended.